Production and Characterization of Chitinases from Thermophilic Bacteria Isolated from Prataan Hot Spring, East Java - Ruth Chrisnasari; Steven Yasaputera; Pauline Christianto; Veronika Ivone Santoso; Tjandra Pantjajani (Institute for Research and Community Services (LPPM) ITB, 2016)
Thermophilic bacteria producing chitinase were collected from Prataan hot spring, East Java, Indonesia and screened. The isolated bacterium was analyzed using 16S rRNA gene sequencing analysis and identified as Paenibacillus sp. The molecular identification was confirmed through morphological and physiological analyses. The production of chitinase was conducted at various incubation times, temperatures, pH and concentrations of colloidal chitin. The optimum condition of the isolate to produce the highest chitinase was 0.9% (w/v) of colloidal chitin (pH 7.0) at 48 °C for 24 hours. The obtained chitinases were optimally active at 55 °C and pH 6.0-7.0. The chitinases were gradually purified by ammonium sulfate precipitation, Sephadex G-100 gel filtration, followed by DEAE